2014
DOI: 10.1080/10410236.2013.837569
|View full text |Cite
|
Sign up to set email alerts
|

“That Was Grown Folks’ Business”: Narrative Reflection and Response in Older Adults’ Family Health History Communication

Abstract: Given the importance of family health history and the pivotal role of older adults in communicating it, this study examines how African American older adults (a) characterize their understandings of health-related conditions in their family histories and (b) rationalize their motivations and constraints for sharing this information with current family members. Using narrative theory as a framework, we illustrate how the participants reflect on prior health-related experiences within the family to respond to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Although health was not commonly discussed in past generations of Black families, the focus group participants stated health communications have significantly increased in Black families and Black communities. These findings were consistent with the Yamasaki and Hovick (2015) study, which reported motivation to improve health communication within Black families resulted from past family experiences of health secrecy of parents. Using focus groups, the men gained insight into their communication experiences as children within their families and how those experiences shaped their perception and willingness to disclose their own diagnosis of prostate cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Although health was not commonly discussed in past generations of Black families, the focus group participants stated health communications have significantly increased in Black families and Black communities. These findings were consistent with the Yamasaki and Hovick (2015) study, which reported motivation to improve health communication within Black families resulted from past family experiences of health secrecy of parents. Using focus groups, the men gained insight into their communication experiences as children within their families and how those experiences shaped their perception and willingness to disclose their own diagnosis of prostate cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies found that Blacks may delay seeking medical care [22] as part of a culture that normalizes privacy regarding medical concerns [23]. Some recipients commented specifically on male avoidance in seeking preventive care and how admitted illness could damage one’s self-perception of strength and autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Women are seen as family health historians and the responsible ones for communicating health information within the family (Koehly et al, 2009; Nycum, Avard, & Knoppers, 2009; Wiseman, Dancyger, & Michie, 2010). A generational pattern has also emerged, with older generations often adopting a sense of responsibility for communicating and sharing information about family health history with younger generations (Ashida & Schafer, 2015; Hovick, Yamasaki; Burton-Chase, & Peterson, 2015; Yamasaki & Hovick, 2015). Cultural differences have also been found, with Latinos and African Americans holding certain beliefs (e.g., shame; fatalism) and values (e.g., maintaining independence; protecting relatives from worry) that are negatively associated with family health history communication (Haggstrom & Shapiro, 2006; Kinney, Gammon, Coworth, Simonsen, & Arce-Laretta, 2010; Yamasaki & Hovick, 2015).…”
Section: Introductionmentioning
confidence: 99%